Ambidexterity: the essence of entrepreneurial competencies and its non-formal learning - M. Ripollés; F. Michavila (Universitat Politècnica de València, 2020)
Despite the worldwide increase in entrepreneurship education offered at universities, there is an ongoing debate whether and under which conditions this type of education contributes to foster students' entrepreneurial competencies. There is no consensus on what entrepreneurial competencies means, neither on the characteristics of the pedagogical interventions needed, especially on what refers to the measurement of these interventions. This paper argues that universities need to develop learning environments in the context of non-formal education. Non-formal education is proposed to fit better with the enhancement of entrepreneurial competencies, as it offers the flexibility required to facilitate experimentation and to allow students to gather entrepreneurial experience. Additionally, in this paper arguments are developed to show how formative evaluation systems suit entrepreneurial pedagogic interventions. Therefore, a comprehensive proposal that facilitates the acquisition of entrepreneurial competencies, the main pedagogical characteristics that should inspire the different educational programs and their relationships with the different types of entrepreneurial competencies are exposed. The article ends with the design of a formative evaluation system that highlights the importance of reflection as an element of the evaluation process and the entrepreneurial learning process.